Misinformation: The Greatest Threat to Democracy-Empowering K-12 Teachers to Build Critical Media Literacy Skills in Students - Levitt, Greg; Grubaugh, Steven (Technium Social Sciences Journal, 2024)
Misinformation poses a significant threat to democratic societies by undermining public trust, increasing polarization, and obstructing informed decision-making. This paper explores the pervasive impact of misinformation on democracy and emphasizes the critical role of K-12 educators in fostering media literacy skills among students. By equipping students with the ability to critically evaluate information, educators can help build a more informed citizenry capable of resisting the influence of falsehoods. The paper discusses strategies for teachers, including building media literacy, teaching critical evaluation methods, leveraging technology responsibly, and fostering a culture of critical thinking and civil discourse. Practical resources for teachers are also highlighted to combat misinformation effectively